2018
DOI: 10.1080/15384101.2018.1482137
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA H19-elevated LIN28B promotes lung cancer progression through sequestering miR-196b

Abstract: LncRNA H19 is involved in the development of multiple cancers. Here, we firstly provide new evidence that H19 can induce LIN28B, a conserved RNA binding protein, to accelerate lung cancer growth through sponging miR-196b. Abundance in LIN28B was observed in clinical lung cancer samples. A positive link was observed between H19 and LIN28B in clinical lung cancer samples. In lung cancer cells, H19 was capable of increasing LIN28B expression. Mechanistically, miR-196b directly targeted LIN28B to inhibit LIN28B ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 46 publications
0
28
1
Order By: Relevance
“…By analyzing the public database, H19 was one of most overexpressed lncRNAs in primary tumor and metastatic tissues compared with adjacent normal tissues in CRC. Aberrant expression of H19 has been demonstrated in various kinds of malignancies including lung cancer, gastric cancer and pancreatic cancer [14][15][16]. Furthermore, Zhou et al reported that H19 lead to epithelial-to-mesenchymal transition (EMT), a pivotal step in cancer metastasis [17], by acting as miRNA sponges to inhibit the functions of related miRNA [18].…”
Section: Introductionmentioning
confidence: 99%
“…By analyzing the public database, H19 was one of most overexpressed lncRNAs in primary tumor and metastatic tissues compared with adjacent normal tissues in CRC. Aberrant expression of H19 has been demonstrated in various kinds of malignancies including lung cancer, gastric cancer and pancreatic cancer [14][15][16]. Furthermore, Zhou et al reported that H19 lead to epithelial-to-mesenchymal transition (EMT), a pivotal step in cancer metastasis [17], by acting as miRNA sponges to inhibit the functions of related miRNA [18].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that upregulation of H19 can induce cell proliferation, invasion, and EMT occurrence by acting as an miRNA sponge and regulating miRNA-203-mediated EMT [66]. Additionally, H19 can induce cell proliferation by promoting the expression of pro-oncogene lin-28 homolog B (LIN28B) via the inhibition of miR-196b expression in A549 and H1299 LC cell lines [71]. H19 can also compete with miR-107 to bind neurofibromin 1 (NF1), which stimulates the development of NSCLC [42,72].…”
Section: Lncrnas In Lung Cancer (Lc)mentioning
confidence: 99%
“…This is due to the sponging of miR-196b by H19, that normally supresses LIN28 mRNA translation. LIN28 expression allowed by H19 leads to the promotion of lung cancer cell proliferation [67]. Similarly, H19 has been found to sponge miR-3126-5p to allow the expression of ERβ receptor in papillary thyroid carcinoma, but also to sponge miR-193b in hepatocellular carcinoma, leading to the activation of MAPK1 and other oncogenes [57,68].…”
Section: H19 Contributes To the Enrichment And Maintenance Of Cscsmentioning
confidence: 90%